Optimization of Donor Lymphocyte Infusion for AML Relapse After Allo-HCT in the Era of New Drugs and Cell Engineering - Ye, Yishan; Yang, Luxin; Yuan, Xiaolin; Huang, He; Luo, Yi (Frontiers in Oncology, 2022)
Donor lymphocyte infusion (DLI) is a key strategy for the treatment of AML relapse after allogeneic hematopoietic cell transplantation (allo-HCT) and has been used for either prophylactic, pre-emptive, or therapeutic purposes. However, the prognosis of these patients remains dismal even after DLI infusion (2-year overall survival, ~25%), and the efficacy is achieved at the cost of toxicities such as graft-versus-host (GVH) disease. Attempts to optimize DLI efficacy and safety, such as dose/timing modification and the use of cytoreduction, before DLI have been performed previously. Recently, a great number of novel targeted and immunomodulatory agents have emerged. Some of them, such as hypomethylating agents, FLT3 and Bcl-2 inhibitors, have been used in combination with DLI, aiming to enhance the graft-versus-leukemia effect. Moreover, manipulation of the DLI graft through cell selection (e.g., donor NK cells) or cell engineering (donor CAR-T cells) has shown potentially superior anti-tumor effects but less GVH effect than conventional DLI in clinical trials. This review summarizes the recent advances on the use of DLI for the prophylaxis/treatment of AML relapse and discusses future strategies which may further improve the treatment efficacy.